New Ankylosaurian Cranial Remains From the Lower Cretaceous (Upper Albian) Toolebuc Formation of Queensland, Australia - Frauenfelder, Timothy G.; Bell, Phil R.; Brougham, Tom; Bevitt, Joseph J.; Bicknell, Russell D. C.; Kear, Benjamin P.; Wroe, Stephen; Campione, Nicolás E. (Frontiers in Earth Science, 2022)
Australian dinosaur research has undergone a renaissance in the last ten years, with growing knowledge of mid-Cretaceous assemblages revealing an endemic high-paleolatitude Gondwanan fauna. One of its most conspicuous members is ankylosaurs, which are rare but nonetheless occur in most Australian dinosaur-bearing formations spanning the uppermost Barremian to lower Cenomanian. Here we describe a partial ankylosaur skull from the marine Toolebuc Formation exposed near Boulia in western Queensland, Australia. This skull represents the oldest ankylosaurian material from Queensland, predating the holotype of Kunbarrasaurus ieversi, which was found in the overlying Allaru Mudstone. The ankylosaur skull is encased in a limestone concretion with the maxillary tooth rows preserved only as impressions. Synchrotron radiation X-ray tomography was used to non-destructively image and reconstruct the specimen in 3D and facilitate virtual preparation of the separate cranial bones. The reconstruction of the skull revealed the vomer, palatines, sections of the ectopterygoids and maxillae, and multiple teeth. The palate has posteriorly positioned choanae that differs from the more anterior placement seen in most other ankylosaurians, but which is shared with K. ieversi, Akainacephalus johnsoni, Cedarpelta bilbeyhallorum, Gobisaurus domoculus, and Panoplosaurus mirus. Phylogenetic analyses place the new cranial material within the recently named basal ankylosaurian clade Parankylosauria together with K. ieversi. This result, together with the anatomical similarities to the holotype of K. ieversi, permits its referral to cf. Kunbarrasaurus sp. This specimen elucidates the palatal anatomy of Australian ankylosaurs and highlights one of the most ubiquitous components of Australian mid-Cretaceous dinosaur faunas.